1984
DOI: 10.2170/jjphysiol.34.679
|View full text |Cite
|
Sign up to set email alerts
|

Constant mechanical efficiency of contractile machinery of canine left ventricle under different loading and inotropic conditions.

Abstract: We have recently proposed that the total mechanical energy generated in each cardiac contraction can be quantified by the systolic pressure-volume area (PVA). PVA is the area in the pressure-volume (P-V) diagram that is circumscribed by the end-systolic and end-diastolic P-V relation curves and the systolic segment of the P-V trajectory. This area has dimensions of energy and comprises the external mechanical work and the elastic potential energy. In the left ventricle of crosscirculated canine hearts, we stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Stroke work was approximated by the product of stroke volume (SV) and end‐systolic pressure (Pes). Ventricular efficiency, defined as the ratio between the ventricular external work and O 2 consumption by the myocardium (VO 2 ), 10 was calculated from the linear relationship of VO 2 to pressure–volume area (PVA): 11–13 …”
Section: Methodsmentioning
confidence: 99%
“…Stroke work was approximated by the product of stroke volume (SV) and end‐systolic pressure (Pes). Ventricular efficiency, defined as the ratio between the ventricular external work and O 2 consumption by the myocardium (VO 2 ), 10 was calculated from the linear relationship of VO 2 to pressure–volume area (PVA): 11–13 …”
Section: Methodsmentioning
confidence: 99%
“…Ventricular efficiency is defined as the ratio between SW and oxygen consumption (Burkhoff and Sagawa 1986). PVA is a linear surrogate of myocardial oxygen consumption (Suga et al 1980(Suga et al , 1983(Suga et al , 1984. PVA is the total mechanical work performed by the ventricle, calculated from the sum of the external stroke work (SWdetermined from the area contained within the PV-loop) that propels the blood from the ventricle and mechanical potential energy (PEthe area bound by the ESPVR and EDPVR) stored in the ventricle at the end of each contraction ( Fig.…”
Section: Animal Modelmentioning
confidence: 99%
“…15 Myocardial efficiency, defined by the relation between total pressure-volume work (pressure-volume area [PVA]) and oxygen consumption, has also been shown to be little influenced by vascular load or ejection history. [16][17][18] We recently reported that lowering vascular resistance could have positive effects on both contractility and efficiency19; however, the relevance of this finding to in situ hearts ejecting into a stiff vasculature is unknown. Other prior studies have attempted to measure in situ effects of aortic stiffening on cardiac function and energetics by replacing the aorta with an artificial conduit or by physically stiffening the native aorta.…”
mentioning
confidence: 99%